Furan Polymers: State of the Art and Perspectives. Issue 6 (3rd February 2022) - Gandini, Alessandro; M. Lacerda, Talita
Abstract: This contribution provides an outlook on the topic of furan polymers, dealing with both its main achievements and the salient recent contributions, together with a critical assessment of their most promising perspectives. Following a brief account of the relevant chemical properties of the furan heterocycle, the main monomers from furfural and hydroxymethylfurfural and their respective polymerization mechanisms are discussed. Chain‐growth polymerizations concentrate on free‐radical and cationic systems, whereas step‐growth polymerizations describe the polycondensation of furfuryl alcohol, polyesters, polyamides, polyurethanes and polyureas, poly(Schiff base)s, epoxy resins, and the polycondensation of 5‐methylfurfural. Finally, the use of the Diels–Alder reaction applied to furan polymer synthesis and modification is reviewed. Abstract : The burgeoning topic of furan polymers evolved quickly, especially within the last decade. The main related achievements are put together here, with a critical assessment of their most promising perspectives. Chain‐growth and step‐growth mechanisms, as well as the Diels–Alder reaction applied to polymer synthesis, allow the design of a wide family of bio‐based furan polymers with tunable properties.